2008
DOI: 10.1530/eje-07-0819
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a clinically homogenous subgroup of benign cortisol-secreting adrenocortical tumors characterized by alterations of the protein kinase A (PKA) subunits and high PKA activity.

Abstract: Objective: The cAMP/protein kinase A (PKA) pathway plays an important role in endocrine tumorigenesis. PKA is a heterotetramer with two regulatory subunits (four genes: PRKAR1A, PRKAR1B, PRKAR2A, PRKAR2B) and two catalytic subunits. Inactivating PRKAR1A mutations have been observed in Carney complex and a subset of adrenocortical tumors (ACT). This study was designed to search for other alterations of PKA in ACT, and to establish their correlation with the clinical characteristics. Methods: In this study, 35 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 35 publications
2
21
0
Order By: Relevance
“…Thus, it remains unclear if the expression of the regulatory subunits influences the specific steroidogenic profile of the three zones of the adrenal cortex. Of note, in some CPA, reduced protein levels of the regulatory subunit IIβ have been previously observed 23, 24 . Here we investigate if the PRKACA mutations leading to hyperactivity of PKA signalling in CPA are associated with the loss of RIIβ protein levels and demonstrate a clear connection between RIIβ protein levels and the mutation status of PRKACA .…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…Thus, it remains unclear if the expression of the regulatory subunits influences the specific steroidogenic profile of the three zones of the adrenal cortex. Of note, in some CPA, reduced protein levels of the regulatory subunit IIβ have been previously observed 23, 24 . Here we investigate if the PRKACA mutations leading to hyperactivity of PKA signalling in CPA are associated with the loss of RIIβ protein levels and demonstrate a clear connection between RIIβ protein levels and the mutation status of PRKACA .…”
Section: Introductionmentioning
confidence: 76%
“…In 2008 two studies had shown that protein expression of the RIIβ subunit of PKA is markedly reduced in CPA compared to other adrenocortical tumours, while no such differences were observed regarding the expression of the other regulatory subunits 23, 24 . There were some discrepancies between the two studies, with Mantovani et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results are matching with Neben and et al results. Expression increase in breast, colorectal and various human nonendocrine cancers (26) and especially in cervical cancer this increased expression is related with poor prognosis. In our study, we determined that PRKAR2A gene is 5 times expressed; also there aren't any studies, which reveal this gene's relation with MM.…”
Section: Discussionmentioning
confidence: 99%